Horrible Harry bugs and the three bears - Kline, Suzy; Remkiewicz, Frank (New York : Scholastic, 2008)
Harry incorporates his fascination with earwigs into Miss Mackle's class project of acting out a fairy tale in front of the other third graders.
Keywords: Children's stories; Fairy tales